Synthesis of Triarylphosphines via Cu-Catalyzed Coupling of Aryl Halides and Acylphosphines - Xu, Minghui; Zhu, Zhengping; Yi, Haojie; Zhu, Hong; Wang, Zhiqian (Synthesis, 2023)
A Cu-catalyzed C(sp2)–P bond forming reaction using an acylphosphine as the phosphorus source is reported; with CuCl2 as the catalyst, 34 examples of aryl iodides and bromides were converted into triarylphosphines in good to excellent yield. A preliminary study of the mechanism was carried out and found that a radical intermediate is not involved. This reaction is an extension of the application of acylphosphines in Cu-catalyzed reactions and shows their potential as a phosphination reagent in the synthesis of tertiary phosphines.
Keywords: Cu catalysis; acylphosphines; C(sp2)–P bond formation; triarylphosphine; phosphination reagent